Extra-enteric Blastocystis infection in a duck - Ilchyshyn, Nicholas P. (J Vet Diagn Invest, 2018)
Cell structures morphologically consistent with Blastocystis were aspirated from a subcutaneous facial swelling in a 13-mo-old pet duck. On PCR analysis and sequencing, the organism was confirmed as Blastocystis sp. subtype 7. Blastocystis is a single-celled protist that is found in the intestinal tract of many species, including mammals, birds, reptiles, amphibians, and insects. A complete understanding of the lifecycle and pathogenesis of the parasite remains elusive. Blastocystis has been implicated in human and animal disease; however, its role is controversial given that it is commonly found among healthy gut microbiota. Infection with Blastocystis outside the intestinal tract has been reported only rarely in humans. Our case of subcutaneous Blastocystis infection in a duck is a novel presentation of a ubiquitous, generally asymptomatic, parasite or commensal of the intestinal tract.